icaA/D Genes and Biofilm Formation of Methicillin-Resistant Staphylococcus aureus in Dr. Soetomo Hospital, Surabaya - Suryanditha, Putu Arya; Rasita, Yoeke Dewi; Debora, Kartuti; Kuntaman, K (Folia Medica Indonesiana, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is a global health concern. One of the factors causing hospital infection is related to the ability of MRSA bacteria to form biofilms. Polysaccharide intercellular adhesin (PIA), encoded by ica gene, have an important role in S. aureus intracellular accumulation and aggregation. The aims of this study was to analyze the relationship between icaA, icaD genes and biofilm production in MRSA carrier and clinical isolate in Dr. Soetomo Hospital Surabaya. This study was an observational study using cross sectional approach. The sample was 47 MRSA isolates is as follow 28 isolates from carrier and 19 were clinical isolates. All of MRSA isolates carried mecA gene. PCR was performed to detect icaA and icaD genes. Biofilm formation was detected using microtiter plate assay (MTP). icaA gene was detected in all isolates whereas icaD gene in 96,4% carrier isolates and all (100%) of clinical isolates. Positive MTP results showed in all (100%) of carrier isolates and 57,9% of clinical isolates. Statistic result was significantly different in biofilm formation between carrier and clinical MRSA isolates. The proportion of positive biofilm formation in isolate with positive icaA/D genes was 82.6%. There was not any association between icaA and icaD gene with biofilm production.